2010
DOI: 10.1007/s00134-010-1860-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simulation-based learning on medication error rates in critically ill patients

Abstract: Simulation-based learning provides a significant advantage to patient care through the reduction of medication administration errors compared to lecture style education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 25 publications
0
89
1
4
Order By: Relevance
“…7,8 Simulation can play an important role for students and healthcare professionals. 5,[13][14][15][16] A prospective randomized controlled trial demonstrated that HFPS improved ACLS performance, and medical residents were more adherent to American Heart Association standards during cardiac arrest events. [17][18][19] High-fidelity simulation in pharmacy education has also been well received with a significant improvement in knowledge and problemsolving skills.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Simulation can play an important role for students and healthcare professionals. 5,[13][14][15][16] A prospective randomized controlled trial demonstrated that HFPS improved ACLS performance, and medical residents were more adherent to American Heart Association standards during cardiac arrest events. [17][18][19] High-fidelity simulation in pharmacy education has also been well received with a significant improvement in knowledge and problemsolving skills.…”
Section: Introductionmentioning
confidence: 99%
“…Following the intervention, the medication administration error rates of nurses in the study group significantly decreased from 30.8% to 4% (p ,0.001) compared to nurses in a control group whose error rates increased from 20.8% to 36.7% (p 5 0.002) over the same period of time. 14 The value of using high-fidelity manikins in pharmacy has been investigated to teach critical thinking, clinical reasoning, and problem-solving skills 7,10,15,16 ; advanced cardiovascular support 17 ; medical emergencies and critical care management 7,9 ; team-working skills and interprofessional working 16,18 ; end of life care 19 ; technical skills; and performance-based pharmacotherapy principles 15,20 In these studies, simulation was mainly used for formative assessment. Also, a variety of assessment methods was used to qualitatively and quantitatively examine the impact of simulation-based learning.…”
Section: Introductionmentioning
confidence: 99%
“…1 Highfidelity patient simulation is effective in the development of confidence, pharmacotherapeutic knowledge, and physical assessment skills [2][3][4] and has a positive impact on patient care. [5][6][7][8][9][10][11] Combining online and simulation-based learning provides an excellent way to enhance skills and knowledge as well as objectively assess knowledge and performance. With patient simulation, students can see and hear a topic, be tested and practice the skills through online assessments, and perform functions of a pharmacist in comprehensive assessments.…”
Section: Introductionmentioning
confidence: 99%